Optimasi Kinerja Pompa Sentrifugal Produk Lokal dengan Modifikasi Impeler dan Analisis visualisasi Aliran - Soeadgihardo Siswantoro; S Sutrisno (Forum Teknik, 2003)
A preliminary  efort to  inrprove  an impeller  design for domestic  centrifugal  pump  with  165 mm  outlet  diameter, semi open impeller  has been  initiated  implementing flow visualization method. The  study was focused on  several  impellers  having  different inlet  and  outlet angles, each of  them  has  the  same blade  thickness.A facitity has  been constructed  to  measure  the  performance for those  impellers  at similar speed,  200b  rpm.  The visualization  technique  applied  in  the  study  was  wet paint  method applying  point  on the  surface  of the  impellers  with several  layers  of dffirent  colors  and wetness.Impellers  hwing  optimum  inlet  ond  outlet angles  have been  identified.Keywords :  impeller, flow visualization